THE OPTIMUM DESIGN OF THE JIB CRANE BY USING FINITE ELEMENT METHOD: บทความวิจัย - Panmongkol, Picha; Leelatanaroek, Wasan; Phuraya, Noppakorn (วารสารวิทยาศาสตร์และเทคโนโลยี มหาวิทยาลัยเซาธ์อีสท์บางกอก, 2023)
In this experiment, the Finite Element Method (FEM) is employed to simulate von Mises Stress, Displacement, and the Factor of Safety (FOS)across three variations of a swing jib crane. The first variation, referred to as Type-1, incorporated a 12t mm stiffener plate and is characterized by the dimensions H150×150×7×10 mm. The second variation, Type-2, is designed without a stiffener plate and has identical dimensions to Type-1:H150×150×7×10 mm. The third and final variation, Type-3, is similar to Type-1 in its use of a 12t mm stiffener plate but differs in its dimensions, which are H100×100×6×8 mm. This study analyzes these three types of swing jib cranes through simulation and statistical evaluation to identify the optimal design in terms of engineering excellence and cost-effectiveness. The distribution of von Mises Stress and displacement within the jib crane structures are investigated, revealing critical stress concentrations at the bolt holes. However, maximum stress levels remained below yield stress thresholds for all crane types. The factor of safety analysis indicates that the Type-3 jib crane is the most optimal, with a Factor of Safety value of 1.5, exceeding recommended standards. Moreover, considering the mass weight and fabrication cost, the Type-3 jib crane is the most cost-effective choice and helps reduce cost by up to 10%. The statistical significance established through ANOVA reveals the significant impact of design on stress distribution, displacement, FOS, and mass weight. Therefore, the Type-3 jib crane is suggested as the most optimal choice for fabrication. A successful load test of the Type-3 jib crane verifies its performance and matches simulated test results.